IMPLEMENTASI AUDIO MUSIK LATAR DAN VOICE OVER PADA VIDEO PERMOHONAN PENERBITAN SERTIFIKAT ELEKTRONIK - Lubis, Yosua; Harlyan, Gendhy Dwi (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2023)
Audio is a sound that can be heard and seen and has an important role in supporting the delivery of narrative messages and providing atmosphere or mood in an animated video. An electronic certificate is a certificate that is electronic in nature. It contains an electronic signature that shows the identity and status of the legal subject of the parties and electronic transactions. Background music and voice-over were applied to a video about electronic certificate issuance as a medium for conveying information to clarify the content of the video. The video was then shown to employees and officials issuing the electronic certificates. The use of Fruity Loops Studio 20 for background music and voice-over is the main focus. It is expected to create original audio so that the video is informative and meaningful. The method used in the implementation of background music audio and voice-over in the application video for the issuance of electronic certificates is the Villamil-Molina method. And then, alpha testing and beta testing were carried out to determine the role of audio in providing information. The research results obtained are in the form of motion graphics.